Three-dimensional S-velocity structure of the crust in the southeast margin of the Tibetan plateau and geodynamic implications. (15th October 2017) - Peng, Hengchu; Yang, Haiyan; Hu, Jiafu; Badal, José
Graphical abstract: Highlights: An accurate 3D image of the S-velocity structure of the crust in the southeast of Tibet has been obtained. An extensive intracrustal low-velocity zone has been detected in the explored area. This wide zone is approximately delimited by the Xiaojiang fault to the east and the Jinshajiang-Red River fault to the west. The detected low-velocity area extends through the Sichuan-Yunnan block. However, no pattern is observed that resembles two low-velocity channels in the area. Abstract: The lower crustal flow model is one of several competing models considered to interpret the growth and expansion of southeastern Tibet. However, the dynamic processes involved in the evolution and deformation of the Tibetan plateau remain poorly understood due to the absence of reliable geophysical observations. In this study, 159 earthquakes of magnitude Ms ≥ 6.2 were selected, which were recorded by 50 permanent broadband stations deployed in southwest China, and 1873 pairs of P-wave receiver functions with high signal-to-noise ratio were isolated. On the basis of a linearized inversion algorithm, a two-step inversion procedure was implemented that not only reduced the dependence of the inversion results on the initial models, but also provided a statistical estimation of the solution. Thus, we obtained an accurate 3D image of the S-wave velocity structure of the crust and uppermost mantle in the southeast margin of the Tibetan plateau. Our results reveal that an extensive intracrustal low-velocity zone spreads beneath southwest China, and further suggest that a lower crustal flow coming from eastern Tibet is blocked by the Jinshajiang-Red River fault to the west and the Xiaojiang fault to the east and extends largely by the Sichuan-Yunnan diamond-shaped block. This crustal flow along the southeastern margin of Tibet does not appear to be restricted to two narrow low-velocity channels as was advanced, but rather reflects the southeastward extrusion of crustal material as a way of tectonic escape.